Performance analysis of routing protocols in heterogeneous network - Mohamed Abdi, Abdirahman (2014)
Rapid growth of wireless networking technologies with in these recent years have led to the emergence of services such as WiFi, WiMAX and LTE that aim to provide flexible and mobile networking solutions. However the future development local area network will have also to include fixed stationary devices that act as infrastructure or backbone nodes to support reliability of wireless services. In such a heterogeneous network, traffic and node density are among the main network conditions that significantly affect the performance analysis of routing protocols. Thus, our study focuses on investigating the performance of Ad hoc On demand Distance Vector (AODV) and Dynamic Source Routing (DSR) routing protocols in the heterogeneous network environment. Optical Micro Network (OMNET++) simulator is used to analyze the delay, throughput and bandwidth utilization performances of two protocols. Our findings reveal that the performance of Ad hoc On-demand Distance Vector (AODV) has high throughput and less delay than Dynamic Source Routing (DSR). However DSR demonstrates bandwidth utilization than AODV. AODV has lower data delay in high dense network because it can reach destination easily while DSR works well in low traffic environment.